(untitled) (The Review of Diabetic Studies, 2024)
Introduction: Saudi Arabian hospitals are moving towards the value-based model of healthcare according to the Saudi Vision 2030, as well as the Health Sector Transformation Program. At the center of this change is the nursing workforce, which forms the greatest professional demographic in the healthcare industry of the Kingdom. Nurse-Patient Ratio (NPR) is a crucial structural parameter of nursing quality; nevertheless, the contribution of these ratios to the specifics of a socio-cultural and demographic situation in Saudi Arabia where the number of expatriates and the volume of national employees is high and is systematically evaluated. Study Objective: The primary goal of this thorough examination is to provide a thorough investigation and organised compilation of existing literature about the effect of Nurse-Patient Ratios (NPR) on the overall quality of care in Saudi Arabia hospitals. Methodology: A systematic search was carried out in five major databases, PubMed, CINAHL, Scopus, Google Scholar, and Saudi Digital Library (SDL). Primary research studies published in 2015-2025 were searched in peer-reviewed studies. The predefined inclusion criteria used in the screening through the PRISMA guidelines was based on the acute care setting in the Kingdom. The information was collected on staffing metrics, negative events in patients, and nurse-reported outcomes. The results of the studies included were subjected to a thematic synthesis. Conclusion: Proper nurse staffing is not only a logistical value but a determining factor of patient safety and workforce sustainability in the Saudi system of healthcare. In order to meet the quality targets of the Vision 2030, the policymakers will need to have standardized and evidence-based staffing requirements which will take into consideration the cultural and communicative intricacies of the Saudi clinical setting.